1947
DOI: 10.1021/ie50456a601
|View full text |Cite
|
Sign up to set email alerts
|

CORRESPONDENCE - Synthesis of DDT with Chlorosulfonic Acid as the Condensation Agent

Abstract: The 30 square foot filter has five auxiliary centrifugal pumps, one vacuum pump, one compressor for refrigeration, one blower, one agitator, and a motor drive; hence no decrease in the speci-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1949
1949
1949
1949

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…chilled saturated NaCl solution to the filtrate from the original water-insoluble crude filter cake vielded 41. 5 Gm. dry sodium pchlorobenzenesulfonate (theoretical weight equivalent to 0.2 mol.…”
Section: Condensation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…chilled saturated NaCl solution to the filtrate from the original water-insoluble crude filter cake vielded 41. 5 Gm. dry sodium pchlorobenzenesulfonate (theoretical weight equivalent to 0.2 mol.…”
Section: Condensation Studiesmentioning
confidence: 99%
“…STUDY of the literature on the synthesis of A DDT indicated that while many condensing agents have been considered, only sulfuric acid (11), chlorosulfonic acid (4, 13), and hydrofluoric acid (15) have been successfully employed in its preparation. The technical production of DDT has been limited to the exclusive use of the h-st-mentioned condensing agent, even though it was pointed out recently that the economic operating limit of this method as expressed in terms of the percentage theoretical yield of pure DDT, is appreciably lower than that by the chlorosulfonic acid method (5). In 1945 an article by Giral and Range1 (7), in an obscure periodical, announced the synthesis of DDT in quantitative yield from chloral and p-chlorobenzenesulfonic acid according to the following reaction : CC13CH( 0 ) +Z~-CIC~H&O~H+H&O, Moreover, these authors postulated that the condensation of chloral with chlorobenzene in the presence of sulfuric acid occurs through the formation of an intermediate compound, p-chlorobenzenesulfonic acid and therefore they believed the quality of the DDT technical product might be improved through the direct synthesis of the insecticide according to the above-indicated equation.…”
mentioning
confidence: 99%